2023
DOI: 10.1038/s41467-023-35874-w
|View full text |Cite
|
Sign up to set email alerts
|

Master mitotic kinases regulate viral genome delivery during papillomavirus cell entry

Abstract: Mitosis induces cellular rearrangements like spindle formation, Golgi fragmentation, and nuclear envelope breakdown. Similar to certain retroviruses, nuclear delivery during entry of human papillomavirus (HPV) genomes is facilitated by mitosis, during which minor capsid protein L2 tethers viral DNA to mitotic chromosomes. However, the mechanism of viral genome delivery and tethering to condensed chromosomes is barely understood. It is unclear, which cellular proteins facilitate this process or how this process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Following nuclear envelope breakdown during mitosis, the L2/vDNA complex enters the nucleus where it associates with chromosomes and remains in vesicles throughout mitosis [ 65 67 ]. Transit of the L2/vDNA complex from the Golgi to mitotic chromosomes is mediated by cyclin-dependent kinase 1- and polo like kinase 1-induced phosphorylation of L2 during G2/M transition [ 68 ]. Interaction with these two key kinases likely triggers a conformational change of L2 to induce tethering to chromatin [ 68 ].…”
Section: Acquisition and Persistence Of Oral Hpvmentioning
confidence: 99%
See 1 more Smart Citation
“…Following nuclear envelope breakdown during mitosis, the L2/vDNA complex enters the nucleus where it associates with chromosomes and remains in vesicles throughout mitosis [ 65 67 ]. Transit of the L2/vDNA complex from the Golgi to mitotic chromosomes is mediated by cyclin-dependent kinase 1- and polo like kinase 1-induced phosphorylation of L2 during G2/M transition [ 68 ]. Interaction with these two key kinases likely triggers a conformational change of L2 to induce tethering to chromatin [ 68 ].…”
Section: Acquisition and Persistence Of Oral Hpvmentioning
confidence: 99%
“…Transit of the L2/vDNA complex from the Golgi to mitotic chromosomes is mediated by cyclin-dependent kinase 1- and polo like kinase 1-induced phosphorylation of L2 during G2/M transition [ 68 ]. Interaction with these two key kinases likely triggers a conformational change of L2 to induce tethering to chromatin [ 68 ]. The nuclear envelope re-forms upon completion of mitosis, the HPV genome is released from its transport vesicle [ 67 ] and undergoes three distinct stages of DNA replication: genome amplification, episomal maintenance, and vegetative amplification.…”
Section: Acquisition and Persistence Of Oral Hpvmentioning
confidence: 99%
“…Several proteins, such as Ran‐binding protein 10, karyopherin alpha, and dynein light chain DYNLT3, can bind to L2 and assist in its transport toward mitotic chromatin 36 . Rizzato's study demonstrated that the CDK1 and PLK1 sequentially phosphorylate the chromosome binding region of L2 to regulate the delivery of HPV viral DNA to mitotic chromatin during mitosis 44 . Additionally, the autophagy adaptor p62 may also have involvement in the nuclear delivery process 43 .…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…The mechanism by which the papillomavirus gene is integrated into the host genome has yet to be fully elucidated. A recent study has shown that phosphorylation of the SSTP (or TSTP) motif, which is highly conserved among papillomaviruses of different animal species in the chromosome binding region of the minor capsid protein L2, by major mitotic kinases CDK1 and PLK1, is involved in the delivery of the viral genome to the host genome during mitosis [ 123 ].…”
Section: Merkel Cell Carcinoma In Catsmentioning
confidence: 99%